Analisis Hadis Tentang Nafkah Istri Dalam Masyarakat Desa Tobing Tinggi Kecamatan Ujung Batu Kabupaten Padang Lawas Utara - Kholija Siregar; Ardiansyah (STAIN MAJENE, 2025)
This study discusses the understanding and application of the hadith regarding the obligation of husbands to provide for their wives in the high tobing village community. Based on Islamic teachings, husbands have the primary responsibility to provide for their wives and families. However, in practice, various factors such as economic conditions, social changes, and women's multiple roles influence this obligation as a result of husbands who are never responsible for family needs. The study used a qualitative approach with interview and observation methods of the local community. The results showed that the discovery of nafkah in the household still faces various challenges, such as husbands who always do things that are prohibited by Islamic law so that husbands ignore their responsibilities as head of the household.